Homotopias finitamente fixadas e pares de homotopias finitamente coincidentes - Cotrim, Fabiana Santos (2011)
In the area of the theory of fixed points and coincidences of Nielsen, this study aims to develop techniques to minimize the set of fixed points in homotopies and the set of coincidences in pairs of homotopies. The techniques are based on Hopf construction for selfmaps of polyhedrons and on the results presented by Helga Schirmer in context of _x-finite homotopies. For pairs of homotopies, we created the concept of coincidences finite and we proved that certain pairs of homotopies can have their set of coincidences minimized in order to become coincidences finite.